Congenital Pulmonary Malformation in Children. (18th July 2012) - Nadeem, Montasser; Elnazir, Basil; Greally, Peter
Abstract : Congenital Pulmonary Malformations (CPMs) are a group of rare lung abnormalities affecting the airways, parenchyma, and vasculature. They represent a spectrum of abnormal development rather than discrete pathological entities. They are caused by aberrant embryological lung development which occurs at different stages of intrauterine life.